Students’ Learning Styles Require Modified Teaching Strategies - Sabiha M. Haq, Shahina Yasmeen , Shabana Ali , Feroze Inayat Gallam (Journal of Rawalpindi Medical College, 2012)
Background: To study the learning styles of medical and dental students. Methods: On the basis of VARK proforma, learning styles of first to third year medical and dental students, were analyzed. Results: Majority of the medical students prefer single learning style.Only 12% preferred multiple learning styles whereas one third of the dental students preferred multiple learning styles. Kinesthetic learning style was the most preferred mode by both medical and dental students. Conclusion: Majority of the medical and dental students have single learning style. Since only one sixth of medical and one third of dental students have multiple learning styles, multiple teaching strategies should be used to address the needs of all the students in one session.